Does the practice of mindfulness reduce somatic symptoms and COVID-19-related anxiety? A community-based survey - Micheli, Noemi; Porcelli, Piero; Barrault-Couchouron, Marion; Dantzer, Cécile (Frontiers in Psychology, 2022)
Objective: Since the beginning of Covid-19 pandemic, several studies have shown an increase of psychological distress in the general population. Previous research demonstrated that high levels of anxiety are associated with reporting more somatic symptoms. The ability to adaptively regulate emotions is essential to deal with stressful situations, and it is one of the main components of mindfulness practice. The aim of the present study was to document the effect of mindfulness practice on somatic symptoms and psychological distress in the context of Covid-19 pandemic. Methods: The study has a descriptive cross-sectional design. During the second wave of Covid-19 pandemic, between November 2020 and January 2021 participants living in France responded to an online survey on the impact of Covid-19 on psychological distress and physical health. The questionnaire included the assessment of Covid-19-related anxiety, mindfulness practice and experience, dispositional mindfulness, somatization, depression, generalized anxiety and emotion regulation. Results: A total of 569 people (mean age = 39.8 years, 90% women) were included in the study. Covid-19 related anxiety was associated with higher levels of somatic symptoms, generalized anxiety and depression. About half of the sample (n = 268, 47%) reported moderate to severe somatic symptoms that were associated with higher levels of depression and anxiety, lower levels of dispositional mindfulness and to the use of maladaptive emotion regulation strategies. Overall, 164 subjects (28.8%) reported practicing meditation. No differences were found in dispositional mindfulness (MAAS score) between beginners and advanced practitioners, regardless of the type, years, frequency and length of practice. Participants with less experience in mindfulness practice reported a significant higher number of somatic symptoms than non-practitioners and a higher use of rumination. Moreover, mindfulness experience was associated with the use of more adaptive emotion regulation strategies. Conclusions: Mindfulness meditation has been promoted as a practice enhancing well-being and helping to cope with the psychological impact of stressful events. However, in a distressing situation as Covid-19 pandemic, a limited experience in mindfulness practices might result in the development or endurance of somatic symptoms. Adequate training and a focus on mindful acceptance, may contribute to enhance the effectiveness of mindfulness practice.